Peran Crisis Management Initiative (CMI) Dalam Resolusi Konflik Antara Gerakan Aceh Merdeka (GAM) dan Pemerintah Indonesia Tahun 2005-2012 - Kurniawan, Rizky Arie (Global and Policy Journal of International Relations, 2016)
ABSTRACTThis study aims to describe the role of the Crisis Management Initiative (CMI) in the resolution of conflict between the Free Aceh Movement (GAM) and the Indonesian government. Post-independence Indonesia in 1945, Aceh felt that they have been colonized by Indonesia to exploit the natural resources and that there is an economic inequality between Aceh and other areas in Indonesia. GAM is formed to fight against the Government of Indonesia (GoI) as the result of the disappointment that has been experienced by the people of Aceh. GAM seeks to liberate Aceh from Indonesia and to restore the rights of the deprived people of Aceh. This study discusses the role of CMI between the GAM-GoI using conflict resolution theory, which focuses on the process to transform a conflict into peace, and also the theory of non-governmental organization’s role, which focuses on the non-governmental organizations as the actors who are able to influence the conflict resolution. Overall, this research argues that the CMI's role in the conflict resolution between GAM-GoI is as mediators, facilitators and observers. The period of the study is limited from the 2005 to 2012. This study uses a descriptive research methodology where the data is presented in detailed manner.Keywords: Crisis Management Initiative, GAM, Government of Indonesia, Conflict Resolution, Role of Non-Governmental OrganizationDOI : https://doi.org/10.33005/jgp.v4i01.1927